An overview of obesity mechanisms in humans: Endocrine regulation of food intake, eating behaviour and common determinants of body weight. Issue 1 (23rd February 2021) - Theilade, Simone; Christensen, Mikkel B.; Vilsbøll, Tina; Knop, Filip K.
Abstract: Obesity is one of the biggest health challenges of the 21st century, already affecting close to 700 million people worldwide, debilitating and shortening lives and costing billions of pounds in healthcare costs and loss of workability. Body weight homeostasis relies on complex biological mechanisms and the development of obesity occurs on a background of genetic susceptibility and an environment promoting increased caloric intake and reduced physical activity. The pathophysiology of common obesity links neuro‐endocrine and metabolic disturbances with behavioural changes, genetics, epigenetics and cultural habits. Also, specific causes of obesity exist, including monogenetic diseases and iatrogenic causes. In this review, we provide an overview of obesity mechanisms in humans with a focus on energy homeostasis, endocrine regulation of food intake and eating behavior, as well as the most common specific causes of obesity.